La lógica estratégica de la proliferación nuclear. Una aproximación teórica - Lahoz Casas, Daniel (2024)
Since the bombings of Hiroshima and Nagasaki in 1945, nuclear proliferation has remained a polarizing issue. While some attribute to it a pacifying effect, others, adopting a more pessimistic stance, underscore its catastrophic potential. This article aims to shed light on the study of the strategic dynamics surrounding this phenomenon by categorizing its key components and exploring the main motivations that push states to obtain nuclear weapons. Since we argue that a state’s likelihood of proliferation is largely determined by the strategic interaction with its adversaries, we employ Game Theory’s models, specifically the “Prisoner’s Dilemma” and the “Deer Hunt”, to discuss the tendencies that may lead towards either a scenario of widespread proliferation or one of coordinated denuclearization.